Sunitinib Combined with Angiotensin-2 Type-1 Receptor Antagonists Induces More Necrosis: A Murine Xenograft Model of Renal Cell Carcinoma. (22nd May 2014) - Verhoest, Grégory; Dolley-Hitze, Thibault; Jouan, Florence; Belaud-Rotureau, Marc-Antoine; Oger, Emmanuel; Lavenu, Audrey; Bensalah, Karim; Arlot-Bonnemains, Yannick; Collet, Nicolas; Rioux-Leclercq, Nathalie; Vigneau, Cécile
Abstract : Background . Angiotensin-2 type-1 receptor antagonists not are only antihypertensive drugs but also can inhibit VEGF production. We hypothesised that adding telmisartan to sunitinib could potentiate the antiangiogenic effects. Material and Methods . 786-O cell lines were injected in nude mice. After tumor development, mice were divided into 4 groups: the first was the control group (DMSO), the second group was treated with sunitinib alone, the third group was treated with telmisartan alone, and the fourth group was treated with the combination. Drugs were orally administered every day for four weeks. Animals were sacrificed after treatment. Blood and tumor tissues were collected for analysis by immunohistochemistry, Western Blot, and ELISA methods. Results . All animals developed a ccRCC and ten in each group were treated. Using a kinetic model, tumors tended to grow slower in the combination group compared to others (P = 0.06 ). Compared to sunitinib alone, the addition of telmisartan significantly increased tissue necrosis (P = 0.038 ). Central microvascular density decreased (P = 0.0038 ) as well as circulating VEGF (P = 0.003 ). There was no significant variation in proliferation or apoptosis markers. Conclusion . The combination of sunitinib and telmisartan revealed an enhancement of the blockage of the VEGF pathway on renal tumor resulting in a decrease in neoangiogenesis and an increase in necrosis.